2022
DOI: 10.1007/s11695-021-05875-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-factor Xa Levels in Female and Male Patients with Obesity After Enoxaparin Application for Thromboprophylaxis

Abstract: Purpose Venous thromboembolic events (VTEs) are common complications after bariatric surgery, and enoxaparin is commonly used to prevent VTEs. The risk for VTEs is sex-specific. Whether enoxaparin application results in similar anti-factor Xa activities (aFXa) in males and females with obesity remains to be determined. We investigated whether our dosage regimen of enoxaparin resulted in similar serum aFXa levels in female and male patients undergoing bariatric surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Most data exist only on the use of enoxaparin for thromboprophylaxis in bariatric surgery. These studies conclude that patients receiving a weight-based enoxaparin prophylaxis are more likely to have their anti-Xa activity in the target range than with a fixed-dose regimen, whereas thrombotic complications are rare [ [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…Most data exist only on the use of enoxaparin for thromboprophylaxis in bariatric surgery. These studies conclude that patients receiving a weight-based enoxaparin prophylaxis are more likely to have their anti-Xa activity in the target range than with a fixed-dose regimen, whereas thrombotic complications are rare [ [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcomes were the incidence of supraprophylactic (supratherapeutic) anti-Xa levels and subprophylactic (subtherapeutic) anti-Xa levels. Although currently controversial ( 12 , 17 , 18 ), the prophylactic and therapeutic levels of anti-Xa are 0.2-0.4 IU/ml and 0.5-1.0 IU/ml, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research shows that the use of a standard dosage of LMWH for prevention in this specific weight group may be inadequate (11)(12)(13). In a large-scale retrospective cohort study, despite receiving chemoprophylaxis, critically ill obese patients had a significantly higher incidence of VTE than nonobese patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…In bariatric surgery, some studies have shown that LMWH at doses higher than standard-dose used in nonobese patients (fixed, adjusted to weight, or to BMI) achieve expected peak anti-Xa levels (between 0.2 and 0.5 IU ml −1 ) more frequently 15–22 . However, the evidence regarding the anti-Xa effect of higher doses of LMWH and heparin on VTE is uncertain 23,24 …”
Section: Rationalementioning
confidence: 99%
“…5,14 In bariatric surgery, some studies have shown that LMWH at doses higher than standard-dose used in nonobese patients (fixed, adjusted to weight, or to BMI) achieve expected peak anti-Xa levels (between 0.2 and 0.5 IU ml À1 ) more frequently. [15][16][17][18][19][20][21][22] However, the evidence regarding the anti-Xa effect of higher doses of LMWH and heparin on VTE is uncertain. 23,24 Although one study has reported a lower incidence of VTE starting LMWH 12 h before laparoscopic bariatric surgery, compared to starting postoperatively, 25 the evidence on the effect of prophylaxis timing is uncertain.…”
mentioning
confidence: 99%